2020
DOI: 10.20341/gb.2020.004
|View full text |Cite
|
Sign up to set email alerts
|

Routing of terrestrial organic matter from the Congo River to the ultimate sink in the abyss: a mass balance approach (André Dumont medallist lecture 2017)

Abstract: We address the role of the Congo River sediment dispersal in exporting and trapping organic carbon into deep offshore sediments. Of particular interest is the Congo submarine canyon, which constitutes a permanent link between the terrestrial sediment sources and the marine sink. The Congo River delivers an annual sediment load of ~40 Tg (including 2 Tg of C) that feed a mud-rich turbidite system. Previous estimates of carbon storage capacity in the Congo turbidite system suggest that the terminal lobe complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 67 publications
(161 reference statements)
0
33
0
Order By: Relevance
“…In the case of freshwater lakes, the required sediment concentration is very low, about 1 kg.m -3 (Mulder and Syvitski 1995). Hyperpycnal flows have been proved to be also an important contributor to the flux of land-derived organic carbon towards distal, central basin areas (Zavala et al 2012;Liu et al 2013;Baudin et al 2017Baudin et al , 2020.…”
Section: Towards a Rational Classification Of Deltas And Their Depositsmentioning
confidence: 99%
“…In the case of freshwater lakes, the required sediment concentration is very low, about 1 kg.m -3 (Mulder and Syvitski 1995). Hyperpycnal flows have been proved to be also an important contributor to the flux of land-derived organic carbon towards distal, central basin areas (Zavala et al 2012;Liu et al 2013;Baudin et al 2017Baudin et al , 2020.…”
Section: Towards a Rational Classification Of Deltas And Their Depositsmentioning
confidence: 99%
“…However, remineralization was shown to occur in small proportions in the Congo system, based on in situ measurements of total oxygen uptake made on the lobe sediments (Rabouille et al, 2019). Finally, we note that undersampling of the Congo Canyon and Channel occurred in past studies due to the difficulty with sampling sandy deposits (Baudin et al, 2020). This undersampling of the canyon and channel may result in underestimation of OC burial rates in the Congo Channel, similar to the Bute Inlet channel where only 30-cm-long sediment cores could be retrieved.…”
Section: Comparison With Larger Deep-sea Turbidity Current Systemsmentioning
confidence: 74%
“…This is the Congo River to the Congo Fan (Baudin et al, , 2020Coynel et al, 2005), where burial rates are calculated over centennial timescales that are comparable to the longer timescales considered in this study. Using a source to sink approach, Baudin et al (2020) found that 33%-69% of the annual OC delivered by the Congo River is buried in the Congo turbidity current system. This burial efficiency is similar to, if slightly lower than, our estimate in Bute Inlet (52%-72%), highlighting the difficulty in closing budgets between river source and marine sinks fed by turbidity currents (Baudin et al, 2020).…”
Section: Comparison With Larger Deep-sea Turbidity Current Systemsmentioning
confidence: 90%
See 2 more Smart Citations